2018
DOI: 10.1155/2018/6981505
|View full text |Cite
|
Sign up to set email alerts
|

Sentry Bioconvertible Inferior Vena Cava Filter: Study of Stages of Incorporation in an Experimental Ovine Model

Abstract: The Sentry inferior vena cava (IVC) filter is designed to provide temporary protection from pulmonary embolism (PE) and then bioconvert to become incorporated in the vessel wall, leaving a patent IVC lumen. Objective. To evaluate the performance and stages of incorporation of the Sentry IVC filter in an ovine model. Methods. Twenty-four bioconvertible devices and 1 control retrievable filter were implanted in the infrarenal IVC of 25 sheep, with extensive daily monitoring and intensive imaging. Vessels and dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…There were no filter-related deaths through 24 months of follow-up. Through 24 months of followup, there was no evidence of late-stage IVC obstruction or thrombosis after filter bioconversion or of thrombogenicity associated with retracted filter arms, which was a finding that confirmed the results of preclinical studies with the device in an experimental ovine model (23). There was no PE experienced by any patient who had thrombus in the filter in the protocolmandated 1-month CT venography (see Appendix C [available online on the article's Supplemental Material page at www.jvir.…”
Section: Discussionsupporting
confidence: 73%
“…There were no filter-related deaths through 24 months of follow-up. Through 24 months of followup, there was no evidence of late-stage IVC obstruction or thrombosis after filter bioconversion or of thrombogenicity associated with retracted filter arms, which was a finding that confirmed the results of preclinical studies with the device in an experimental ovine model (23). There was no PE experienced by any patient who had thrombus in the filter in the protocolmandated 1-month CT venography (see Appendix C [available online on the article's Supplemental Material page at www.jvir.…”
Section: Discussionsupporting
confidence: 73%
“…The results of the animal studies have been reported by Gaines et al [59]. In all 24 animals that received study devices, deployment and positioning in the filtering configuration in the center of the IVC lumen were successful, and pre- and posttermination examinations confirmed that all filters had bioconverted as intended, leaving the IVC lumens patent.…”
Section: Sentry Ivc Filter Description and Performancementioning
confidence: 61%
“…The reasons for the nonconversion of the Sentry IVC filter in 4 patients as of 12-month follow-up cannot be accurately determined. In preclinical studies, the presence of fibrin strands was occasionally noted at the ends of filter arm, and such a circumstance could delay or prevent separation of the arms [59]. In context, however, the 96.4% rate of bioconversion far surpasses reported retrieval rates for IVC filters [3, 9, 10].…”
Section: Sentry Ivc Filter Description and Performancementioning
confidence: 99%
See 1 more Smart Citation
“…devices were all bioconverted and stably incorporated, leaving all IVCs patent (23). Interim results are reported here from a prospective trial undertaken to evaluate the safety and efficacy of the Sentry IVC filter in patients with documented DVT or PE, or at temporary risk of developing DVT or PE, and with a contraindication to anticoagulation.…”
mentioning
confidence: 99%